Pacing profiles relative to interchanges in elite rugby league - Highton, J.; Waldron, M.; Daniels, M.; Twist, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Differences in high-intensity (> 14 km/h) movement between playing positions in elite rugby league match play are well documented (Sykes et al., 2011; Waldron et al., 2011), yet little information exists on the exercise profile of interchanged players. Understanding exercise intensity during multiple interchanges is important for match conditioning, but also offers an opportunity to explore the potential for pacing in team sports due to the unstable nature of the exercise end-point (Edwards & Noakes, 2009). Accordingly, the aim of this study was to document pacing profiles of elite rugby league players relative to the nature of their playing bout. Methods: Thirty-five performances from 18 elite males during 14 Engage Super League matches were analysed. Movement characteristics and heart rate (HR) were recorded via a portable 5 Hz GPS device (SPI-Pro; 5Hz, GPSports, Canberra, Australia). Match performances were analysed by quartile and separated in to three categories: whole match (n = 19; players who completed ? 80 min), interchange 1 (n = 16; the initial match play bout; mean = 20.2 ± 3.9 min) and interchange 2 (n = 9; players coming on for their second bout; mean = 22.5 ± 11.0 min). Results: In interchange 2, high intensity m/min declined from quartile 1 to quartile 3 only (18 ± 4.1 c.f. 13.4 ± 5 m/min), whilst whole match players declined from quartile 1 (18.3 ± 4.7 m/min) to quartile 4 (14 ± 4.6 m/min). In contrast, interchange 1 players had a higher initial high intensity m/min in quartile 1 (24.2 ± 7.9 m/min), which declined progressively between match quartiles. Whole match players` %HRpeak progressively decreased across match quartiles, and was lower at quartile 3 (81.7 ± 4.5%) and 4 (79.9 ± 7%) compared to interchange 2 (86.3 ± 5.4% and 90.3 ± 2.9%) and at quartile 3 compared to interchange 1 (87.3 ± 4.2%). Discussion: In agreement with previous rugby league data (Sykes et al., 2011), whole match players demonstrate a subtle progressive decline in high intensity movement. In contrast, players in their first interchange adopt a higher initial exercise intensity followed by a rapid decline. During their second interchange, players exercise at an intensity which is closer to that of whole match players and that can be maintained until the exercise end-point. These data have implications for rugby league interchange strategy and the development of match-specific conditioning programs, and provide preliminary evidence of variable macro-pacing strategies in rugby league (Edwards & Noakes, 2009).